BETTER SAFE THAN SORRY: Magistrates’ views on the Domestic Violence Act - Artz, Lillian (SA crime quarterly, 2016)
As part of an ongoing project to monitor the implementation of the Domestic Violence Act, this article focuses on the role of magistrates. The impression exists that magistrates have a tendency to judge domestic violence matters conservatively. But research shows that most take a ‘better safe, than sorry’ approach in granting particular conditions in protection orders. The general sentiment is that it makes more sense to have an allinclusive protection order than one that will be subject to variation at a later stage.